2011
DOI: 10.14693/jdi.v18i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Odontectomy Cases in an Indonesian Teaching Hospital

Abstract: Extraction of impacted teeth has became one of the most common procedure in oral surgery. Objective: This study aimed to observe the frequency and distribution of odontectomy cases in Oral Surgery Clinic of RSGMP FKG UI. Methods: A descriptive study using dental record as secondary data at RSGMP FKG UI. Results: There were 145 odontectomy in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has also been found that the modern diet does not offer a decided effort in mastication, resulting in loss of growth stimulation of jaws, and thus, the modern man has impacted and unerupted teeth (Santosh, 2015). Impaction may occur because there is no path of eruption due to tooth development in an abnormal position or obstruction by a physical barrier such as another tooth, odontogenic cyst or tumour (Soeprapto, Latif, & Julia, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the modern diet does not offer a decided effort in mastication, resulting in loss of growth stimulation of jaws, and thus, the modern man has impacted and unerupted teeth (Santosh, 2015). Impaction may occur because there is no path of eruption due to tooth development in an abnormal position or obstruction by a physical barrier such as another tooth, odontogenic cyst or tumour (Soeprapto, Latif, & Julia, 2011).…”
Section: Introductionmentioning
confidence: 99%